IMPROVING CALIBRATION AND MEASUREMENT CAPABILITY (CMC) OF PSYCHROMETER CALIBRATION - Arfan Sindhu Tistomo; Purwowibowo -; Rcahman Soleh; Melati Azizka Fajria; Ocka Hedrony (LIPI Press, Anggota IKAPI, 2018)
The improvement of Calibration Measurement Capability (CMC) for Psychrometer calibration has been done through calibrating a homemade psychrometer with two platinum resistance sensors as its dry and wet bulb thermometers. The calibration range covers 15 %rh to 90 %rh in a temperature range from 25 °C to 65 °C. The uncertainty budget is evaluated from the individual quantity uncertainty following Ferrel equation. As results, not only the existing CMC is greatly improved from 5 %rh to 1.8 %rh but also the calibration uncertainty at each set point is in accordance to the review criteria uncertainty values for submitting relative humidity CMCs to the Appendix C of Bureau International des Poids et Mesures (BIPM).